Self-Assessment dalam Kegiatan Diskusi Problem-Based Learning Fakultas Kedokteran: Kajian Naratif - Rose Feri; Marcellus Simadibrata; Anwar Jusuf (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2015)
Background: Student peformance assessment during problem-based learning (PBL) discussion is still debatable. One of the assessments that applies adult learning principle is self-assessment  (SA). In fact, many medical schools prefer to use tutor assessment than SA because it is considered less accurate. Many studies have reported that the accuracy of SA is poor because of their own lack of knowledge and SA skills.  This literature review aims to explore deeper in SA and its basic principles in designing SA instrument for PBL discussion in medical school.Method: This study was conducted using narrative review method. Ten articles were reviewed. Five articles were chosen from google search engine and the other five from medical education textbooks.Results: SA is the ability of a student to observe, analyze and assess his own performance based on the criteria and he determines a way to fix it. SA skills that have been practiced during  PBL discussions will equip the students to become future health professionals who are competent in determining their own continuous professional development (CPD) programs. When designing a SA instrument, one needs to explore these five main issues, including acceptance, accuracy, power, feasibility and context.Conclusion: SA is the most effective assessment to assess a student’s achievement in PBL discussion if implemented properly. The completion of SA should be made in the normal context and one must explore the five main issues constantly so that SA can be done properly and well.